RPC based 5D tracking concept for high multiplicity tracking trigger. (20th January 2017) - Aielli, G.; Camarri, P.; Cardarelli, R.; Ciaccio, A. Di; Distante, L.; Liberti, B.; Paolozzi, L.; Pastori, E.; Santonico, R.
Abstract: The recently approved High Luminosity LHC project (HL-LHC) and the future colliders proposals present a challenging experimental scenario, dominated by high pileup, radiation background and a bunch crossing time possibly shorter than 5 ns. This holds as well for muon systems, where RPCs can play a fundamental role in the design of the future experiments. The RPCs, thanks to their high space-time granularity, allows a sparse representation of the particle hits, in a very large parametric space containing, in addition to 3D spatial localization, also the pulse time and width associated to the avalanche charge. This 5D representation of the hits can be exploited to improve the performance of complex detectors such as muon systems and increase the discovery potential of a future experiment, by allowing a better track pileup rejection and sharper momentum resolution, an effective measurement of the particle velocity, to tag and trigger the non-ultrarelativistic particles, and the detection local multiple track events in close proximity without ambiguities. Moreover, due to the fast response, typically for RPCs of the order of a few ns, this information can be provided promptly to the lowest level trigger. We will discus theoretically and experimentally the principles and performance of this original method.